Cryptococcal cerebrospinal fluid shunt infection treated with fluconazole - Daniel Eymard; François Lebel (Canadian Journal of Infectious Diseases)
A 37-year-old woman with a cadaveric renal allotransplantation required intra-cranial shunting devices after a presumptive episode of tuberculous meningitis. Six months later, she developed a culture-proven cryptococcal meningitis. Without having her ventriculo-auricular shunt removed, she was successfully treated with a short course of amphotericin B (335 mg) and flucytosine (nine days) followed by prolonged therapy with oral fluconazole (400 mg daily for 72 days). Three years post treatment she had no evidence of relapse, and normal renal graft function.